2018
DOI: 10.7554/elife.34389
|View full text |Cite
|
Sign up to set email alerts
|

ZMYND10 functions in a chaperone relay during axonemal dynein assembly

Abstract: Molecular chaperones promote the folding and macromolecular assembly of a diverse set of ‘client’ proteins. How ubiquitous chaperone machineries direct their activities towards specific sets of substrates is unclear. Through the use of mouse genetics, imaging and quantitative proteomics we uncover that ZMYND10 is a novel co-chaperone that confers specificity for the FKBP8-HSP90 chaperone complex towards axonemal dynein clients required for cilia motility. Loss of ZMYND10 perturbs the chaperoning of axonemal dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 61 publications
3
37
2
Order By: Relevance
“…Previous studies have established a strong genetic link between loss or mutation of DNAAF7 and a combined outer and inner dynein arms defect in model organisms (fly, medaka, Xenopus, mouse) and humans (PCD, CILD22) [35,36,72,73]. DNAAF7 interacts with RuvBL2 [58] and LRRC6 [35,58,74]. It was shown that the C-terminal fragment of DNAAF7 and the CS domain of LRRC6 were necessary for this interaction [35].…”
Section: Dnaafs and Their Function In Dynein Arm Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have established a strong genetic link between loss or mutation of DNAAF7 and a combined outer and inner dynein arms defect in model organisms (fly, medaka, Xenopus, mouse) and humans (PCD, CILD22) [35,36,72,73]. DNAAF7 interacts with RuvBL2 [58] and LRRC6 [35,58,74]. It was shown that the C-terminal fragment of DNAAF7 and the CS domain of LRRC6 were necessary for this interaction [35].…”
Section: Dnaafs and Their Function In Dynein Arm Assemblymentioning
confidence: 99%
“…DNAAF7 also forms complexes with C21ORF59 and DNAAF4, IDAs' dynein light chain, and components of ODAs such as TCTEX1D1 (Tctex1 domain-containing D1) and DNAI1 (Table 2) [58]. Recently, Mali and co-workers [74] revealed that, in murine cells, DNAAF7 can form a novel chaperone complex comprising DNAAF7, FKBP8, and Hsp90, which can take part in the maturation of dynein heavy chains.…”
Section: Dnaafs and Their Function In Dynein Arm Assemblymentioning
confidence: 99%
“…Moreover, genetic ablation of the Hsp90 co-chaperone Ruvbl1/2 results in defective dynein arm assembly in zebrafish and mice (Li et al, 2017; Zhao et al, 2013). More recently, work in diverse model animals has led to a model in which DNAAFs function as part of a ‘chaperone relay,’ with distinct DNAAFs mediating specific steps in the dynein assembly process (Cho et al, 2018; Mali et al, 2018; Olcese et al, 2017; Yamaguchi et al, 2018; Zur Lage et al, 2018). Several of these studies suggest that the DNAAFs and chaperones act together in cytosolic ‘foci’ (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mali et al, 2018). Thus, understanding the role of RNA-associated proteins in DynAPs is an important specific challenge, while development of methods for systematic identification of RAPs from animal tissues will be broadly useful.…”
mentioning
confidence: 99%